A broadband miniaturized ultra‐thin tri‐band bandpass FSS with triangular layout. Issue 7 (12th April 2019) - Yu, Qiming; Liu, Shaobin; Kong, Xiangkun; Bian, Borui
Abstract: A tri‐band broadband ultra‐thin miniaturized highly selective bandpass frequency‐selective surface (FSS) has been proposed by using coupled resonance. The proposed FSS is a three‐layer periodic arrays consisting of three metal layers that are separated from each other by two dielectric substrates. Two exterior layers are composed of gridded‐double hexagonal loops (G‐DHLs), while the middle layer is composed of double hexagonal loops (DHLs) structure. The second passband has a relative bandwidth of more than 20%, exhibiting broadband characteristics. Due to the superior bandwidth of the hexagon loop, the design FSS can achieve both broadband and low insertion loss characteristics. The FSS show stable incident angles response and wide out‐of‐band rejection performance over a wide range of incidence angle of 60° for both TE and TM polarizations. The wide and sharp out‐of‐band rejection behavior is caused by multi‐transmission zeros on both sides of each passband. The equivalent circuit model of the FSS is provided to analyze its operating principle. The prototype of this FSS is simulated, fabricated, and measured. The measured results show a good agreement with its theoretical analysis and simulation.